The Role of Health Education in Promotion of Health Care Waste Management in Khartoum North Teaching Hospital - Ahmed Abu-Rayyan1 , Waed Alahmad2 , Fatima Fadul ALI Osman3 , Kamal Elbssir M Ali4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study was conducted as a quasi-experimental design in Khartoum North teaching hospital to assess therole of health education in the promotion of health care waste management. A sample size of (103) targetedworkers (cleaners) were used in the investigation. Data collected was analyzed using the T-test and chisquare test by computer using SPSS. The results revealed remarkable improvement in the knowledge ofthe respondents, as regards the hazards of the health care waste (53%-100%) before the intervention, afterthe intervention, it increased to 100% showing highly significant change. The opinion of the respondents touse the protective clothes ranging from (45% - 100%) before the intervention, rose after the intervention to(70.5% – 100%) showing significant change. The practice of workers about touching contaminated cottonand linen with patient body fluids was 16.7% before the intervention, after the intervention only 7.4% touchthe waste showing significant change.